Spanish sources concerning the 1693 earthquake in Sicily - F. Rodriguez de la Torre (Annals of Geophysics, 1995)
When the great 1693 earthquake occurred, Sicily was a viceroyalty of Spain. In order to find primary and direct sources, the Archivo General de Simancas has to be investigated. Due to the lack of extensive and adequate catalogues it is difficult search amongst the millions of documents filed there. The author located among numerous bundles of papers of different Sections. a total of 238 manuscripts (with 850 pages) and 4 printed edicts related to the 1693 earthquake. All the gathered information offers good prospects of true knowledge on many aspects related to the seismic catastrophe: perception area. number of victims, ruin of towns, list of aftershocks. reconstruction. health and public order problems, and all those problems that surround a great historic earthquake (economic, political, social and religious).